Culture of Speech Development in Preschool - Mashkhura, Razakova (European Journal of Life Safety and Stability (2660-9630), 2021)
Dialogue, creativity, cognition, self-development - these are the fundamental components that are involved in the sphere of attention of the teacher when he turns to the problem of speech development of a preschooler. These are the foundations on which modern preschool didactics in general is built and which constitute the foundation of the basic program for the development of a preschool child.The upbringing of clear speech in preschool children is a task of great social significance, and both parents and teachers should be aware of its seriousness.